The Water Balance in Arctic and Subarctic Regions. Annotated Bibliography and Preliminary Assessment. - Dingman,S. Lawrence (1973)
The hydrological cycle plays a central role in geobiological and near-surface geological processes and in the energy balance of the earth. It is of crucial importance to many vital practical problems relative to man and his environment. This is especially true in arctic and subarctic regions, where knowledge of hydrologic processes is particularly limited. The introductory section of this report discusses the global hydrologic cycle and summarizes current estimates of the quantities of water involved in various portions of it. Following this, the definitions and boundaries of the arctic and subarctic are reviewed; a map showing these boundaries and annotations of a number of publications dealing with this problem are also presented. The main part of the report gives several hundred annotations of reports that directly discuss elements of the water balance in arctic and subarctic regions. These annotations are grouped by geographic area: the Northern Hemisphere, Europe, the U.S.S.R., Alaska, Canada, and Greenland and Iceland. For each area, annotations are presented according to water-balance elements: precipitation, evapotranspiration, runoff, streamflow, groundwater contributions to runoff, and changes in glacial storage. (Modified author abstract)